A Simple Technique For Estimation of Reservoir Permeability Which Includes The Absorption Effect of Synthetic Seismic Reflection Data - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Abstract Relationships among elastic parameters and rock properties, and ultimate reservoir parameters have been established in continuum mechanics and rock physics. Therefore, it should be possible to estimate reservoir permeability from the seismic data. We used Sismanto 's method based on Biot's solution of wave equation in an elastic porous medium and the approximations ofTurgut-Yamamoto to allow an establishment of a linear relationship between attenuation coefficient or amplitude ratio as afunction of the inverse of the square offrequency. The slope of this function includes the permeability. It can be shown that this technique agrees to the measurement of the permeability of a porous medium from seismic waveforms. We examined this technique to estimate the reservoir permeability by using synthetic seismogram data. The result show that has an error less than 5 %, it means that the study of permeability estimation from surface seismic data is possible by using an accurate calibration step.